Developing a Single Window to Facilitate Trade in Senegal - Diagne, Ibrahima (World Bank, Washington, DC, 2012)
In 1995 a reform group headed by Senegal's Ministry of trade introduced a single window system for electronic trade facilitation as part of a reform agenda to improve the country's business environment. Launched in 2004, the system transformed customs clearance, streamlining the process through transparent, electronic transactions initiated by a single request from the importer or exporter. Traders could collect and process the necessary documents and authorizations prior to customs declaration in about half a day rather than the four days required before the system was implemented. With its real-time data, government agencies could better monitor and control transactions, contributing to more secure transactions and revenues. This note highlights key issues in Senegal's decision to develop a customized system and offers lessons for governments in managing diverse stakeholder requirements and expectations.